The height of the men`s winners FIVB Beach Volleyball in relation to specialization and court dimensions - Tili, M.; Giatsis, G. (Journal of Human Sport & Exercise, 2011)
The purpose of this study was to find and compare the heights of the men FIVB Beach Volleyball winners in relation to their specialization and court dimensions (9×9 m or 8×8 m). The heights of men`s winners of all FIVB Beach Volleyball (BV) tournaments held between 1987 and 2010 were recorded. The winners were then split into three groups according to their specialization: Defenders (DE), Blockers (BL) without any specialization (No Specialization - NS). Post-hoc Anova test was conducted to determine if there is difference in the winners` height in relation to their specialization and the court dimensions (9×9 and 8×8). Overall, 91 players from 16 countries have won the 257 FIVB BV tournaments. Of the 257 tournaments, 115 were held in 9×9 courts and 142 in 8×8 courts. Of the winners, 44 were defenders, 38 were blockers and 9 had no specialization. The players of all winning teams in 8×8 courts had specialization. The average height of the winners was 192.7 ± 5.3 cm. The shortest winner was 180 cm and the tallest 206 cm. The one way ANOVA indicated that there were significant differences (F(2,88) = 34.071, p<0.001) between the defenders, blockers and no specialization players. The Post Hoc Scheffe indicated significant differences between the DE (M=189.3, SD=3.7 cm) and BL (M=196.7, SD=4.6 cm), as between BL and the NS (M=192.2, SD=2.5 cm). Also, significant differences were found (F(4,99) = 24.286, p<0.001) between the DE9x9, DE8x8, BL9x9, BL8x8 and NS. The Post Hoc Scheffe indicated significant differences (p<0.001) between the DE9x9 (M=188.6, SD=4.1 cm) and BL9x9 (M=194.0, SD=3.8 cm), as between DE9x9 and BL8x8 (M=198.0, SD=4.1 cm). Furthermore, significant differences were found (p<0.05) between BL8x8 and BL9x9. No significant differences were found (p=0.506) between DE9x9, DE8x8. Significant difference were found between NS (M=192.1, SD=2.7 cm) and DE8x8. The independent t-test found significant difference (t(18)=3.215, p<0.01) between the 10 first blockers in victories at 8x8 m (M=199.4, SD=4.1) and 9x9 m (M=193.5, SD=4.1). Overall, regarding player specialization, blockers were taller than defenders in both court dimensions. Although blockers in 8×8 courts were taller than those in 9×9 courts, no significant difference was found in defenders. Smaller court dimensions seem to favored taller players in top level world Beach Volleyball because of the larger importance of blocking and the reduced need for agility. The data at hand certifies the new somatometric requirements for blockers in Beach Volleyball.